Does fear of infection affect people’s dental attendance during COVID-19? A Chinese example to examine the association between COVID anxiety and dental anxiety - Yuan, Siyang; Zheng, Yuanna; Sun, Zhe; Humphris, Gerry (Frontiers in Oral Health, 2023)
Introduction Little is known about the psychological and behavioural effect of COVID-19 pandemic on patients and their reaction to dental visiting. Patients may delay attendance due to fears of contracting the corona virus at the dentist. The study aims to confirm the psychometric properties of the two COVID-19 scales and then use dental patient responses to assess the associations between the COVID-19 Anxiety Scale (CAS), dental anxiety (MDAS) and the clinical care COVID-19 Anxiety (CCAS). Methods A cross-sectional study was conducted among 503 patients visiting a polyclinic of a stomatological hospital in East China in 2020. Patients completed a survey consisting of demographical information, dental attendance, COVID-19 Anxiety Scale, Clinical Care COVID-19 Anxiety Scale and Modified Dental Anxiety Scale. Confirmatory factor analysis was conducted to determine the psychometric characteristics. A further structural model was tested with the combined measurement model and a path analysis was calculated. Results The sample (n = 503) consisted of more women than men (63% vs. 37%). A fifth of the sample (21%) claimed regular dental attendance and just over a third (35%) reported delaying their dental visit due to the pandemic. Our analysis showed that both CAS and CCAS possessed a unidimensional structure. The MDAS was divided into anticipatory and treatment components as separate latent variables. The anticipatory component (MDAS_A) had some association to CCAS through its expression on treatment dental anxiety (MDAS_T). General anxiety about COVID (CAS) had a direct effect on CCAS. The fit statistics were acceptable [Chi-square = 183.27, df = 68, p < .001; CFI = 0.973; RMSEA = 0.058 (95%CIs: 0.048–0.068)] and the Standardised Root Mean Square Residuals (SRMR) index was 0.041. Discussion The Clinical Care COVID-19 Anxiety has shown satisfactory psychometric properties. Both dental anxiety and general anxiety about the pandemic have strong associations to patients’ fear of contracting corona virus when using dental facilities. Our study has practical implications to help healthcare providers better understand how environmental stressors influence patients’ overall concerns on infection risks and appropriate dental treatments during the pandemic.